Identification and characterization of striking multiple‐insecticide resistance in a Tetranychus urticae field population from Greece. Issue 2 (6th November 2020) - Papapostolou, Kyriaki Maria; Riga, Maria; Charamis, Jason; Skoufa, Evangelia; Souchlas, Vassilis; Ilias, Aris; Dermauw, Wannes; Ioannidis, Panagiotis; Van Leeuwen, Thomas; Vontas, John
Abstract: BACKGROUND: Tetranychus urticae is a notorious crop pest with a worldwide distribution that has developed resistance to a wide range of acaricides. Here, we investigated the resistance levels of a T. urticae population collected from an ornamental greenhouse in Peloponnese, Greece, and analyzed its resistance mechanisms at the molecular level. RESULTS: Toxicological assays showed resistance against compounds with different modes of action, with resistance ratios of: 89‐fold for abamectin; > 1000‐fold for clofentezine; > 5000‐fold for etoxazole; 27‐fold for fenpyroximate and pyridaben; 20‐ and 36‐fold for spirodiclofen and spirotetramat, respectively; and 116‐ and > 500‐fold for cyenopyrafen and cyflumetofen, respectively. Bioassays with synergists indicated the involvement of detoxification enzymes in resistance to abamectin, but not to cyflumetofen and spirodiclofen. RNA sequencing (RNA‐seq) analysis showed significant over‐expression of several genes encoding detoxification enzymes such as cytochrome P450 monooxygenases and UDP‐glycosyltransferases, which have been previously associated with acaricide resistance. Known target‐site resistance mutations were identified in acetyl‐choline esterase, chitin synthase 1 and NDUFS7/psst, but putative novel resistance mutations were also discovered in targets such as glutamate‐gated chloride channel subunit 3 . Interestingly, target‐site resistance mutations against pyrethroids or bifenazate were not identified, possibly indicating a recent reduced selection pressure in Greece, as well as a possible opportunity to rotate these chemistries. CONCLUSION: We identified and characterized a striking case of multiple acaricide resistance in a field population of T. urticae . Exceptionally strong resistance phenotypes, with accumulation of multiple resistance mutations and over‐expression of P450s and other detoxification genes in the same field population are reported. Abstract : A Tetranychus urticae field population from Greece shows striking resistance levels against multiple acaricides with different modes of action, due to accumulated target‐site mutations and over‐expression of detoxification genes. © 2020 Society of Chemical Industry